Penerimaan pendengar terhadap penceramah dari luar negara: Kajian di Masjid Al-Falah USJ 9, Selangor / Nor Shahida Shahrel - Nor Shahida , Shahrel (2018)
This research discussed on audience’s acceptance towards the foreign preachers at Masjid Al-Falah USJ 9 (MAF USJ 9), Selangor. The purpose of this study is to review the concept of Islamic public lectures and the types of audience acceptance towards foreign preachers at MAF USJ 9, to identify the implementation of Islamic public lectures activities which involve foreign preachers at MAF USJ 9 plus to analysis the audience acceptances towards foreign preachers at MAF USJ 9. The method that been used for the research are the methodologies of library findings and field research. 240 sets of survey questions had been circulated to respondents who used to follow the Islamic public lectures which were conducted by foreign preachers at MAF USJ 9. Meanwhile, interview session was conducted with Imam 1 MAF USJ 9 (Islamic priest of MAF USJ 9) for obtaining the background of the mosque information, the way of public lectures has been conducted as well as the level of public’s acceptance towards the foreign preachers at MAF USJ 9, Selangor. The research findings found that six aspects have been identified to influent audience’s acceptance aspects towards the foreign preachers, namely, the roles and contributions of mosque, foreign preachers’ attributes, the charismatic and the content of the lectures, the understanding of the Islamic public lectures as well as the credibility of the foreign preachers. The result shows that the presence of foreign preachers in giving Islamic public lectures at MAF USJ 9 are being well accepted. This is because, the audience acceptances play important roles in order to attract other people to join the Islamic public lectures at MAF USJ 9 that being conducted by foreign preachers.